Meticulous Plasma Isolation is Essential to Avoid False Low-Level Viraemia in Roche Cobas HIV-1 Viral Load Assays. Issue 3 (April 2018) - Mortier, Virginie; Vancoillie, Leen; Dauwe, Kenny; Staelens, Delfien; Demecheleer, Els; Schauvliege, Marlies; Dinakis, Sylvie; Van Maerken, Tom; Dessilly, Géraldine; Ruelle, Jean; Verhofstede, Chris
Background: Pre-analytical sample processing is often overlooked as a potential cause of inaccurate assay results. Here we demonstrate how plasma, extracted from standard EDTA-containing blood collection tubes, may contain traces of blood cells consequently resulting in a false low-level HIV-1 viral load when using Roche Cobas HIV-1 assays. Methods: The presence of human DNA in Roche Cobas 4800 RNA extracts and in RNA extracts from the Abbott HIV-1 RealTime assay was assessed by quantifying the human albumin gene by means of quantitative PCR. RNA was extracted from plasma samples before and after an additional centrifugation and tested for viral load and DNA contamination. The relation between total DNA content and viral load was defined. Results: Elevated concentrations of genomic DNA were detected in 28 out of 100 Cobas 4800 extracts and were significantly more frequent in samples processed outside of the AIDS Reference Laboratory. An association between genomic DNA presence and spurious low-level viraemia results was demonstrated. Supplementary centrifugation of plasma before RNA extraction eliminated the contamination and the false viraemia. Conclusions: Plasma isolated from standard EDTA-containing blood collection tubes may contain traces of HIV DNA leading to false viral load results above the clinical cutoff. Supplementary centrifugation of plasma before viral load analysis may eliminate the occurrence of this spurious low-level viraemia.